Immunogenetics of primary Sjögren's syndrome in Colombians (2005)
Objective: Data concerning the immunogenetic characteristics of primary Sjögren’s syndrome (SS) in Latin-Americans are scarce. A research project centered on primary SS in Colombians was initiated in January 1996 to better define these characteristics.MethodsTAP, HLA, IL-10, and microsatellites on 6p21.3 genotyping was performed by polymerase chain reaction techniques. Immunohistochemistry for Bcl-2 antagonist/killer (Bak) was performed. Autoantibodies and serum level of cytokines (IL-10, TNF-?, IFN-?, IL-4, and IL-12p70) were determined by enzyme-linked immunosorbent assay.ResultsThe HLA-DRB1*0301-DQB1*0201 haplotype was associated with disease (OR = 4.3, 95% CI: 1.6 to 11.9, P = 0.002), with a more severe histopathologic picture, and with the presence of anti-Ro and anti-La antibodies. D6S439 microsatellite polymorphism was associated with primary SS in an HLA-independent manner. The most likely gene related to the D6S439 chromosomal location appears to be BAK-1, which codes for Bak protein, expressed in salivary gland’s infiltrate from patients with primary SS but not in controls. IL-10 and IFN-? concentrations were significantly higher in patients than in controls (P < 0.01). IL-10 correlated with titers of IgA rheumatoid factor, anti-Ro, and anti-La antibodies, and with the severity of lymphocytic infiltrate (r > 0.3, P < 0.04). Patients who produced high IL-10 levels had significantly more episodes of cutaneous vasculitis and a higher proportion the IL-10.G9 allele.ConclusionsThe HLA-DRB1*0301-DQB1*0201 haplotype and IL-10 participate in the histopathological progression of SS, autoantibody production, and clinical manifestations. Bak protein and its gene polymorphism may participate in the pathology and susceptibility of disease. HLA and cytokine (IL-10 and IFN-?) manipulation may be helpful in treating patients with primary SS.